Comparison between the effect of flipped classroom teaching and traditional classroom teaching in learning and satisfaction of students in microbiology course - Mojgan Mohammadimehr (Mashhad University of Medical Sciences, 2023)
Background: The flipped classroom is an alternative educational approach that emphasizes the student-centered teaching method. The purpose of this research was to compare the flipped classroom (FC) teaching method with the traditional classroom (TC) teaching method on the learning and satisfaction of students Aja University of Medical Sciences in the microbiology course.Method: This interventional study was conducted in 2022 at the paramedical faculty of the Army University of Medical Sciences. The participants in the study were surgical technician students.  Evaluation of students' learning was done using MCQ test (pre-test and post-test). The level of satisfaction was measured through a 5-point Likert questionnaire made by the researcher. Data were analyzed with SPSS version 19 software.Results: The results of the study showed that there was a significant difference between the average learning of the intervention group, FC=0.82±9.30, and the average learning of the comparison group, TC=3.96±1.39.) P=0.0001). Also, there was a significant difference between the scores of the satisfaction level of the students of the FC group=4.69±0.358 and the average scores of the comparison group TC=2.530±0.863 (P<0.05).Conclusion: The results of the research showed that teaching using the flipped classroom method in the microbiology course of the surgical technician students increased the learning and satisfaction of the students compared to the traditional teaching method.